ANALISA TEGANGAN PIPA PADA INSTRUMENT AIR DALAM SISTEM PEMIPAAN FASILITAS NUKLIR - Budi Santoso (BATAN, 2013)
PIPE STRESS ANAL YSIS ON THE INSTRUMENT AIR IN NUCLEAR FACILITIES PIPE WORK. Piping stress analysis on Instrument Air System have been performed. Analysis carried out to estimate the provision of sufficient flexibility in the piping system to ensure that the heat expansion and contraction of the pipe is still in the allowable stress range. The stress analysis can be used to determine the location and type of support that will be installed. The stress calculation was carried out utilizing the CAESAR